Checkpoint signaling, base excision repair, and PARP promote survival of colon cancer cells treated with 5-fluorodeoxyuridine but not 5-fluorouracil. - Liyi Geng (PLoS ONE, 2011)
The fluoropyrimidines 5-fluorouracil (5-FU) and FdUrd (5-fluorodeoxyuridine; floxuridine) are the backbone of chemotherapy regimens for colon cancer and other tumors. Despite their widespread use, it remains unclear how these agents kill tumor cells. Here, we have analyzed the checkpoint and DNA repair pathways that affect colon tumor responses to 5-FU and FdUrd. These studies demonstrate that both FdUrd and 5-FU activate the ATR and ATM checkpoint signaling pathways, indicating that they cause genotoxic damage. Notably, however, depletion of ATM or ATR does not sensitize colon cancer cells to 5-FU, whereas these checkpoint pathways promote the survival of cells treated with FdUrd, suggesting that FdUrd exerts cytotoxicity by disrupting DNA replication and/or inducing DNA damage, whereas 5-FU does not. We also found that disabling the base excision (BER) repair pathway by depleting XRCC1 or APE1 sensitized colon cancer cells to FdUrd but not 5-FU. Consistent with a role for the BER pathway, we show that small molecule poly(ADP-ribose) polymerase 1/2 (PARP) inhibitors, AZD2281 and ABT-888, remarkably sensitized both mismatch repair (MMR)-proficient and -deficient colon cancer cell lines to FdUrd but not to 5-FU. Taken together, these studies demonstrate that the roles of genotoxin-induced checkpoint signaling and DNA repair differ significantly for these agents and also suggest a novel approach to colon cancer therapy in which FdUrd is combined with a small molecule PARP inhibitor.